Anxiety and depression in frontline health care workers during the outbreak of Covid-19. (September 2021) - Xing, Li-qun; Xu, Min-ling; Sun, Jia; Wang, Qin-Xia; Ge, Dan-dan; Jiang, Ming-ming; Du, Wenjun; Li, Qiang
Background: The pandemic of coronavirus disease (Covid-19) seriously impacts the health and well-being of all of us. Aims: We aim to assess the psychological impact of Covid-19 on frontline health care workers (HCWs), including anxiety, depression and stress of threat of the disease. Method: The study was a cross-sectional survey among the frontline HCWs in a hospital at Jinan, China. Data were collected through an anonymous, self-rated questionnaire, including basic demographic data, a 10-item Covid-19 stress questionnaire, the Self-Rating Anxiety Scale (SAS) and the Self-Rating Depression Scale (SDS). The risk and rate of anxiety, depression and stress of Covid-19 were estimated. Results: Among the 309 participants, there were 88 (28.5%) with anxiety and 172 (56.0%) with depression. Multivariate logistic regression analyses showed that age ⩽ 30 years, age > 30 to 45 years, working in confirmed case isolation wards, and worrying about disinfection measures being not sufficient were independently associated with anxiety with an odds ratio (95% confidence interval, CI) of 4.4 (1.6–12.2), 3.1 (1.1–8.8), 2.3 (1.4–4.0) and 2.5 (1.5–4.3), respectively; age ⩽ 30 years, age > 30 to 45 years, nurse and worrying about disinfection measure being not sufficient were independently associated with depression with an odds ratio (95% CI) of 3.8 (1.8–7.8), 2.7 (1.3–5.7), 2.5 (1.1–5.6) and 2.1 (1.3–3.5), respectively. Conclusions: A high prevalence of anxiety and depression was found among frontline HCWs during the COVID-19 outbreak. More psychological care should be given to young staffs and nurses. Measures to prevent professional exposure is important for HCWs' physical and mental health.